Counter Productive Work Behaviour and Organizational Productivity of Selected Public Organizations in Cross River State: A Theoretical Review - Bernard Samuel Eventus; Nkamare Stephen Ekpo; Ogar Godwin Wonah; Emefiele Charles Chike; Atimba Oboko. I; Egede Samuel Mofam (Law and Economy, 2024)
The purpose of the study was to examine counter productive work behavior and organizational productivity in selected public organizations. A study of Calabar, Ugep and Ikom local government council in Cross River State. The specific objectives were to: examine the extent to which sabotage behavior can affect organizational productivity; examine how theft can affect organizational productivity; and to determine how withdrawal can affect organizational productivity. This study adopted theoretical review methods. Information was gathered using textbooks, journals, published and unpublished journals, libraries and internet applications. Based on the theoretical review, the following findings were revealed thus: there was a significant relationship between sabotage behavior and organizational productivity, there was a significant relationship between theft behavior and organizational productivity, and there was a significant relationship between withdrawal behavior and organizational productivity. In line with the findings, the study recommended that organizations should organise regular enlightenment programmes and formulate appropriate HR policies that would help reduce the level of counterproductive work behaviors among employees. Managers should endeavor to limit the effect and pervasiveness of detrimental behaviors.